“They Just Signed and Stamped Papers”: Understanding the Erasmus Student Experiences - Nada, Cosmin Ionut; Ploner, Josef; Esteki, Laleh (Journal of International Students, 2022)
Erasmus mobility has become an important feature of higher education in Europe and beyond, with the potential to generate significant changes at individual, institutional and systemic levels. More than three decades after the foundation of this successful program, evaluations reveal that, despite notable progress, several aspects of the Erasmus student experience can be further improved. Based on the lived experiences of Erasmus alumni, in this article, we explore recurrent challenges that emerge in educational mobility and how they could be better addressed. Three key dimensions are identified in the qualitative accounts of former Erasmus students and analyzed in light of previous research: mobility preparation, institutional support for integration, and recognition of study abroad.